Tooling with ethics in technology: a scoping review of responsible research and innovation tools - Julian “Iñaki” Goñi; Eugenia Rodrigues; Maria Jesus Parga; Martín Illanes; María José Millán (Journal of Responsible Innovation)
The operationalisation of Responsible Research and Innovation is increasingly associated with ethical toolkits. However, scholars remain critical of those toolkits, often referring to them as theoretically problematic, toothless, or too instrumental. Moreover, toolkits imply ideological commitments that are not necessarily made explicit. In this scoping review, we analyse 127 tools designed for technology ethics as part of the RRI Project. We find that (1) these tools tend to frame responsibility as general training or aimed at the development phase of technologies, while monitoring is underrepresented. (2) These toolkits often lack substantive conceptualisations of ethics ignoring contested paradigms. (3) Emerging digital and biotechnologies are over-represented in relation to other socio-technical infrastructures, and (4) there is a risk of a PDF-ization of ethics, as most toolkits are materially constructed as reading material and checklists. We conclude by presenting prompt questions to reflectively reconsider how we design ethical toolkits for technology.